Perancangan Peta Wisata Interaktif Kota Sidoarjo dengan Menggunakan Desain Landmark yang Ceria - Arva Rangga Yudhistira; Masnuna Masnuna (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of information technology has become an integral part of modern tourism development. Interactive tourist maps have proven to be an effective tool in guiding travelers to explore tourist destinations. This research focuses on designing an innovative and appealing tourist map for the city of Sidoarjo, utilizing cheerful landmark designs. The development method involves user needs analysis, selection of representative landmarks, and the implementation of attractive and user-friendly graphic designs. This interactive tourist map is designed to be accessible through digital platforms, enabling users to plan their journeys more efficiently. The selected landmarks not only serve as location markers but are also designed with cheerful aesthetics to enhance the user experience. The map is equipped with interactive features such as detailed information about each landmark, the best travel routes, as well as reviews and recommendations from previous users. It is expected that the design of this interactive tourist map will make a positive contribution to promoting tourism in the city of Sidoarjo and enhancing traveler satisfaction through an engaging and informative experience. Furthermore, the use of cheerful landmark designs is anticipated to create a strong visual identity, setting it apart from tourist destinations in other cities.